Multi-objective Optimization for Cascade Utilization of Palm Waste in Malaysia using Augmented ∈-constraint Method - Wong, Khai Jian (Italian Association of Chemical Engineering - AIDIC, 2021)
Palm waste has gained traction in the energy industry due to its wide availability. Despite its vast potential as feedstock for downstream industries, palm wastes are still inadequately utilized in Malaysia. Conventional disposal practices of palm waste are economically inefficient and environmentally unfavorable. This study adopted the multi-objective linear programming approach to design the optimal palm waste utilization pathway in Malaysia using the General Algebraic Modeling System, which maximizes profit and minimizes greenhouse gas (GHG) emissions. The 5th Pareto solution (composting: 79.31 %; anaerobic digestion (AD): 10.05 %; pelletizing: 0.35 %; briquetting: 0.37 %; biomass combined heat and power: 9.47 %; dried long fiber production: 0.42 %; carbonization: 0.02 %) that has a net profit of 5.02 x 109 MYR/y and net GHG emissions of -1.6 x 107 t CO2-eq/y is the most viable as it satisfies both objectives to a degree of satisfaction of 0.77. The 1st and 2nd Pareto solution allocates 8.74 x 109 t of solid palm wastes to electricity and heat generation and can achieve the renewable energy target under the biomass category set by the Malaysian government. 3.72 x 107 - 5.16 x 107 t of palm oil mill effluent allocated to AD in the 9th, 10th, and 11th Pareto solutions can achieve the RE target under the biogas category. This study provides insights on the best allocation of palm waste for the stakeholders to devise a proper strategy for effective palm waste utilization that is economically and environmentally viable.